The Contribution of Student Ecoliteracy to Build Environmental Caring Behavior in Senior High School - Suharja, Asrul; Setiawan, Iwan; Nandi, Nandi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This paper aims to describe the contribution of eco-literacy to building environmental caring behavior in Senior High School 1 Bandung. In capital urban of west java have an issue with a variety of environmental damage, such as uncontrolled land use conversion and rising anthropogenic disaster. Thus the environment needs humans for its sustainability. The study used two variables that, include the student’s eco-literacy level and environmental caring behavior level. This research used a survey method with descriptive analysis through a quantitative approach. Primary data comes from direct interviews, surveys, and questionnaires, with secondary data coming from journals, books, and school documentation. Populations and samples were all students in 2nd grade with a total of four classes from social majors. The data analysis techniques used a normality test, linearity test, coefficient of determination R square test, F-test, and t-test. The results of this paper show the student’s eco-literacy has a middle category level and the environmental caring behavior of the students has a middle category level. The development of eco-literacy must be evaluated by educational units indefinitely to build environmental caring behavior at a high category level.